Preparation of Aloe vera extract-loaded chitosan nanoparticles for the controlled delivery of extract phytochemicals in carbon tetrachloride-induced liver injury rat model - Omar Ashraf; Alyaa Farid; Gehan Safwat (Beni-Suef University Journal of Basic and Applied Sciences)
Abstract Background A significant contributing factor to liver damage is drug consumption. Phytochemicals of Aloe vera extract are effective against a variety of diseases. Consequently, this study aimed to create chitosan nanoparticles (chi NPs) that were loaded with Aloe vera extract (ALV extract) to increase the delivery of the extract's bioactive materials. ALV extract, chi NPs, and Aloe vera extract-loaded chitosan nanoparticles (ALV-chi NPs) underwent anti-oxidant, anti-inflammatory, and cytotoxicity tests. The preventive and therapeutic effects of ALV-chi NPs against carbon tetrachloride (CCl4)-induced liver injury were assessed using a male Sprague Dawley rat model. Results Our findings demonstrated that the synthesis of ALV-chi NPs was a promising option for combining the therapeutic benefits of both ALV extract (included in its phytochemicals) and chi NPs. ALV-chi NPs have a uniformly distributed smooth shape with a size of 48.3 ± 2.97 nm, similar to the hydrodynamic size (50.9 ± 0.07 nm), and a surface charge of 38.16 mV. At a 1000 μg/mL concentration, ALV-chi NPs showed high DPPH scavenging % and a high hemolysis inhibition %. At 75 μg/mL, ALV-chi NPs showed lower PTT (63.7 s) than ALV extract (71.2 s). The phenolic components and flavonoids in the extract were released under controlled conditions throughout time, and their bioavailability was enhanced by loading the extract on chi NPs. Conclusions Among all tested formulations, ALV-chi NPs demonstrated superior efficacy, showing 95.4% DPPH scavenging (vs. 91.8% for free extract), 94.1% hemolysis inhibition (comparable to indomethacin), and optimal hepatoprotection in CCl4-induced liver injury. ALV-chi NPs ameliorated the raised levels of liver function parameters, pro-inflammatory cytokines, and intracellular apoptotic proteins. Graphical abstract